Efektivitas Media Memo Ring Note Book Dalam Pembelajaran Hiragana Pada Siswa SMA - Firdausyah, Rosyane; Arni, Rita (Universitas Negeri Padang, 2024)
In learning Japanese letters, hiragana is one of the basics that students must understand and master. In its implementation, there are several problems faced by students when learning basic hiragana which totals 46 letters. Based on interviews were conducted with the teacher concerned, as well as interviews with 10th-grade students across Japanese language interests at Padang 4 Public High School, the results showed that there were many 10th grade students who experienced difficulties in mastering hiragana, namely, because hiragana has more letters than Latin letters. There are several hiragana that have a similar form, and in writing hiragana it must be following the order of the strokes, so a more varied teaching method and media were needed so that students could more easily understand hiragana. The use of memo ring note book media makes it possible to overcome this problem. The purpose of this study was to describe the level of effectiveness of memo ring note book media on hiragana mastery of grade 10 students across Japanese language interests at SMA Negeri 4 Padang. This research is a quantitative research type of experiment with a pre-experimental design type of one-group pre-test post-test design. Data was taken using a purposive sampling technique, namely class X IIS 1 totaling 35 people. Based on the results of the t-test, it was concluded that H1 was accepted at a significant level of 0.05 because the sig value <0.05 (0.000 <0.05), which means that mastery of hiragana in the post-test is much different from the pre-test. In other words, the use of memo ring note book media is effectively used in learning hiragana.